2022
DOI: 10.3390/agriculture12040553
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Approaches to Investigate Molecular Mechanisms in Peach Post-Harvest Ripening

Abstract: Peach post-harvest ripening is a complex developmental process controlled by a plethora of genetic and epigenetic factors. Specifically, it leads to protein, lipid and nucleic acid degradation, all resulting in cell death. Substantial research has been directed at investigating peach regulatory mechanisms underlying genomic, metabolomic and transcriptomic modifications occurring during this stage, and much progress has been made thanks to the advent of Next Generation Sequencing technologies. This review is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 145 publications
0
13
0
Order By: Relevance
“…Here expression of patterns of ATG8 and ATG4 genes were similar to those reported previously for the later stages of ripening ( Sánchez-Sevilla et al., 2021 ) with ATG8 expression increasing while ATG4 expression fell between the white and red stages of ripening. Fruits here were harvested at the red ripe stage so the increase in ATG8 expression could be related to continued ripening during storage which is known to occur in climacteric fruit such as peach ( Sirangelo et al., 2022 ). However, the rise in expression between day 1 and day 5 of storage may also indicate that autophagy is increasing as the fruit tissue begins to run out of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Here expression of patterns of ATG8 and ATG4 genes were similar to those reported previously for the later stages of ripening ( Sánchez-Sevilla et al., 2021 ) with ATG8 expression increasing while ATG4 expression fell between the white and red stages of ripening. Fruits here were harvested at the red ripe stage so the increase in ATG8 expression could be related to continued ripening during storage which is known to occur in climacteric fruit such as peach ( Sirangelo et al., 2022 ). However, the rise in expression between day 1 and day 5 of storage may also indicate that autophagy is increasing as the fruit tissue begins to run out of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…High throughput technologies have also facilitated the generation of extensive omics datasets ( Mora-Poblete et al., 2023 ) eventually, increasing the number of studies involving omics data in fruit postharvest ( Belay and James Caleb, 2022 ). Despite all these technological advances, some key aspects of fruits postharvest processes are not fully understood, including CIs ( Sirangelo et al., 2022 ).…”
Section: Integrated Omics For Studying Chilling Injury Development An...mentioning
confidence: 99%
“…Molecular level information could serve as signalling molecules that alter the biochemical process and the consecutive quality changes in the fruit ( Lara et al, 2022 ). Recent advances in high-throughput technologies such as, transcriptomic, proteomic and metabolomics enables qualitative monitoring and understanding of biological processes and allow determination of their various states on genomic scales (Belay, Caleb, Vorster, Heerden, & Opara et al, 2020; Mathabe, Belay, Ndlovu, & Caleb et al, 2020; Tang, Chen, Hu, Deng, Chen, & Li et al, 2018; Sirangelo et al, 2022 ; Xie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the above studies highlighted that the integrated omics approach provides a better knowledge to understand various molecular mechanisms at the whole genome level. In addition, the benefit of integrated omics analysis for postharvest research has been suggested by various studies ( Chen et al, 2017 , Yun et al, 2019 , Sirangelo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation